ANALISA PENGARUH KAMPUH PENGELASAN DAN PERLAKUAN PANAS TERHADAP SIFAT MEKANIK SAMBUNGAN LAS BAJA SUP9 - I Made Mara; Tri Rachmanto; Syamsul Hadi (Energy, Materials and Product Design, 2023)
The development of science and technology which is growing rapidly greatly affects industries that produce machine elements that use steel as the main raw material, steel is widely used in construction. This has caused many mechanics to join steel using the SMAW process without regard to the welding method and mechanical properties which causes the steel not to be connected perfectly, thereby endangering safety. The purpose of this study was to see the effect of seam variation V, K and X and normalizing, quenching and no heat treatment on the mechanical properties of welded joints in SUP9 steel. From the variation of seam and heat treatment, there were 9 combinations with 3 repetitions. The results of this study indicate that the weld seam and heat treatment affect the tensile strength and impact price of SUP9 steel. The most optimal treatment to produce high tensile strength is seam variation X with quenching heat treatment with ASTM E8 specimen shape having an average tensile stress value of 84.23 Kgf/mm2, and for the most optimal treatment to produce high impact values ​​is variation of seam X with normalizing heat treatment with specimen form ASTM E23 has an average impact value of 1.11 J/mm2.